2021
DOI: 10.1162/qss_a_00127
|View full text |Cite
|
Sign up to set email alerts
|

Universality of citation distributions: A new understanding

Abstract: Universality of scaled citation distributions was claimed a decade ago (F. Radicchi, S. Fortunato, and C. Castellano, PNAS, 105(45), 17268 (2008)) but its theoretical justification has been lacking so far. Here, we study citation distributions for three disciplines- Physics, Economics, and Mathematics- and assess them using our explanatory model of citation dynamics. The model posits that the citation count of a paper is determined by its fitness- the attribute, which, for most papers, is set at the moment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 43 publications
(75 reference statements)
1
4
0
1
Order By: Relevance
“…S4 ). This result is in line with numerous prior studies that identified a similar range of for papers in journals ( 18 20 ), institutions ( 20 ), fields ( 21 23 ), as well as Mendeley readerships ( 24 ) and patent citations ( 25 ).…”
Section: Resultssupporting
confidence: 91%
“…S4 ). This result is in line with numerous prior studies that identified a similar range of for papers in journals ( 18 20 ), institutions ( 20 ), fields ( 21 23 ), as well as Mendeley readerships ( 24 ) and patent citations ( 25 ).…”
Section: Resultssupporting
confidence: 91%
“…For example, for DOIs published between 2010-14 (n = 731, 696), 425, 268 are cited only once (58%), and only 25, 190 are cited 10 or more times (3.4%). Prior research using conventional bibliographic databases have investigated possible statistical distributions that model citation data (Brzezinski, 2015;Eom & Fortunato, 2011;Golosovsky, 2021;Thelwall, 2016), although there is some disagreement on whether powerlaw, log-normal or negative binomial distributions are best. Results vary depending on time period and discipline analysed, database used, and if documents with zero citations are included.…”
Section: How Long Does It Take Research Articles To Accumulate Policy...mentioning
confidence: 99%
“…How can one measure these functions? The fitness distribution can be determined from the analysis of citation distributions in different citation windows (Golosovsky, 2021) while M dir (t) can be found from the analysis of the direct and indirect citations garnered by the papers in the collection. On another hand, M dir (t) can be found from the analysis of the reference lists of papers.…”
Section: The Model Of Citation Dynamics and The Uncitedness Ratiomentioning
confidence: 99%
“…the remaining parameters of citation dynamics, we used our full stochastic model and the previously found aging function A(t) (Golosovsky, 2021) and fitted the citation distributions for each category in the year 2017. We assumed the log-normal reduced fitness distribution and used its width σ as a fitting parameter.…”
Section: Broad Scientific Categoriesmentioning
confidence: 99%
See 1 more Smart Citation